Systemic microvascular dysfunction in microvascular and vasospastic angina. (27th August 2018) - Ford, Thomas J; Rocchiccioli, Paul; Good, Richard; McEntegart, Margaret; Eteiba, Hany; Watkins, Stuart; Shaukat, Aadil; Lindsay, Mitchell; Robertson, Keith; Hood, Stuart; Yii, Eric; Sidik, Novalia; et al.
Abstract: Aims: Coronary microvascular dysfunction and/or vasospasm are potential causes of ischaemia in patients with no obstructive coronary artery disease (INOCA). We tested the hypothesis that these patients also have functional abnormalities in peripheral small arteries. Methods and results: Patients were prospectively enrolled and categorised as having microvascular angina (MVA), vasospastic angina (VSA) or normal control based on invasive coronary artery function tests incorporating probes of endothelial and endothelial-independent function (acetylcholine and adenosine). Gluteal biopsies of subcutaneous fat were performed in 81 subjects (62 years, 69% female, 59 MVA, 11 VSA, and 11 controls). Resistance arteries were dissected enabling study using wire myography. Maximum relaxation to ACh (endothelial function) was reduced in MVA vs. controls [median 77.6 vs. 98.7%; 95% confidence interval (CI) of difference 2.3–38%; P  = 0.0047]. Endothelium-independent relaxation [sodium nitroprusside (SNP)] was similar between all groups. The maximum contractile response to endothelin-1 (ET-1) was greater in MVA (median 121%) vs. controls (100%; 95% CI of median difference 4.7–45%, P  = 0.015). Response to the thromboxane agonist, U46619, was also greater in MVA (143%) vs. controls (109%; 95% CI of difference 13–57%, P  = 0.003). Patients with VSA had similar abnormal patterns of peripheral vascular reactivity including reduced maximum relaxation to ACh (median 79.0% vs. 98.7%; P  = 0.03) and increased response to constrictor agonists including ET-1 (median 125% vs. 100%; P  = 0.02). In all groups, resistance arteries were ≈50-fold more sensitive to the constrictor effects of ET-1 compared with U46619. Conclusions: Systemic microvascular abnormalities are common in patients with MVA and VSA. These mechanisms may involve ET-1 and were characterized by endothelial dysfunction and enhanced vasoconstriction. Clinical trial registration: ClinicalTrials.gov registration is NCT03193294.